Sevak՚s Interpretation of the Poetic Series (“Let There Be Light”) - Bekmezyan, Astghik (Bulletin of Yerevan University B: Philology, 2025)
The poetic series represents a unique system of textual construction and imagery, expanding the artistic sound-based meaning-speech imagery-thought-formulation system through the juxtaposition of similar structures in diverse forms, thus creating a polyphonic (multi-voiced) domain for presenting the theme. The possibilities for aesthetic perception are much more intrinsic and content-bearing. Paruyr Sevak’s "Let There Be Light" collection is the poet’s "artistic testament-summary," where he presents his creative system, bringing together all areas of his concerns regarding the world, reality, and people. The textological and comparative analysis of this multi-layered poetic series allows us to conclude that the "Let There Be Light" series, following all the rules of classical perception—unified theme, chronological identical domain, lyrical hero’s personality unity, harmonious imagery, structural rhythmic completeness—attains emphasized individualized layers in the Sevak’s interpretative domain. It manifests a unique application of intertextuality, a novel interpretation, the personalization of the lyrical hero across all series, and a pronounced, specialized, concrete poetic rereading of universal themes with the multi-tiered elaboration of the subject. The series is also interesting because each separate series within this "large" series can be and is a complete whole, yet based on the aforementioned main features of the series, it forms part of a broader, comprehensive problematics, thus representing one cohesive idea’s artistic presentation. Another characteristic is that each sub-series within the overall series includes other sub-sub-series—series within a series, series within a series within a series—that also appear with their specific and general attributes. In other words, while the poetic series is usually perceived as a unidirectional developing and expanding process, in this case, we encounter an original "woven" structure, where the thematic-ideological, structural linearly predictable flow is periodically interrupted by the introduction of seemingly unexpected new thoughts, images, and the lyrical hero, ultimately presenting a situation that fits within the general logical framework of the series, thus creating a new shade, a new perspective. This article is one of the manifestations of textological research in this field.